REKONSTRUKSI EKO-ETIMON BUDAYA KULINER - Rusyda Nazhirah Yunus (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2019)
This study discusses the reconstruction of eco-etimon culinary culture in the Malay community of Tanjung Pura. The aim of this study was to find out the eco-etymon reconstruction of culture in spicy pulp ingredients, their lingual forms and proto reconstruction of the spicy pulp ingredients. This research uses descriptive qualitative methods. The data of this study are words contained in the spicy porridge ingredients of Tanjung Pura Malay community, as well as data obtained from interviews. Then some lexicon of spicy porridge from Karo, and Aceh. Data is collected by note-taking technique, which is to record ingredients from spicy porridge and interviews with informants around the data source. The data analysis technique in this study was carried out by collecting lexicons of spicy pulp, reconstructing the lexicon and the function of spicy pulp, interviewing informants about the existence of the lexicon. Then compare the pattern of sound changes (reconstruction implications) of several lexicons in spicy porridge ingredients. The results of the analysis indicate that the encoding of spicy porridge ingredients by Tanjungpura Malay ancestors in the form of lexicalisation and grammaticalisation is included in compound words and expression metaphors. The reconstruction of language forms and functions of spicy porridge ingredients. BA, BK, and BM have reconstruction based on the type of sound change.